2018
DOI: 10.1128/mra.01189-18
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequence of a Brucella melitensis Strain Isolated from Sheep in Saudi Arabia

Abstract: The intracellular Gram-negative bacterium Brucella melitensis causes a zoonotic disease in humans originating from animals. Here, we report the whole-genome sequence (WGS) of Brucella melitensis strain KSA_BM_07, isolated from sheep in March 2017 in Huraymila, Kingdom of Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…As the genome of B. melitensis is highly conserved and isolates from the same region, including in the Israeli Negev desert, tightly cluster together, high resolution for accurate phylogenetic analysis is very important for this particular organism in regard to epidemiological or outbreak investigations [ 13 , 14 ]. For the investigation of specific genes in other clinically-relevant organisms, more research is needed, as while this study found that the ONP platform was consistent in identifying virulence genes, recent studies have noted that ONP technology had inconsistent performance regarding the detection of antimicrobial resistance genes in Gram-negative bacteria when compared to Illumina technology [ 4 , 9 , 59 ]. Overall, the findings of this study suggest that in operational settings where information is needed on the virulence genes of B. melitensis , stand-alone long-read sequencing provides comparable data to short-read sequencing in a shorter amount of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the genome of B. melitensis is highly conserved and isolates from the same region, including in the Israeli Negev desert, tightly cluster together, high resolution for accurate phylogenetic analysis is very important for this particular organism in regard to epidemiological or outbreak investigations [ 13 , 14 ]. For the investigation of specific genes in other clinically-relevant organisms, more research is needed, as while this study found that the ONP platform was consistent in identifying virulence genes, recent studies have noted that ONP technology had inconsistent performance regarding the detection of antimicrobial resistance genes in Gram-negative bacteria when compared to Illumina technology [ 4 , 9 , 59 ]. Overall, the findings of this study suggest that in operational settings where information is needed on the virulence genes of B. melitensis , stand-alone long-read sequencing provides comparable data to short-read sequencing in a shorter amount of time.…”
Section: Discussionmentioning
confidence: 99%
“…Brucella melitensis is a key zoonotic bacterial species that is a driver of brucellosis infections, including in the Middle East [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Brucellosis is an under-diagnosed systemic infection; it is estimated that approximately 90% of human cases go undiagnosed [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%